2017
DOI: 10.1002/pssr.201700133
|View full text |Cite
|
Sign up to set email alerts
|

Powerful recombination centers resulting from reactions of hydrogen with carbon–oxygen defects in n‐type Czochralski‐grown silicon

Abstract: It has been acknowledged for over 50 years that treatments with hydrogen can improve silicon semiconductor devices. In recent years, these have been used to an advantage in silicon solar cells reducing the loss of photo‐generated carriers at the silicon surface or at the silicon interface with dielectrics. However, we have found that in some types of silicon the in‐diffusion of hydrogen can result in the formation of powerful recombination centers composed of carbon, oxygen, and hydrogen which reduce the carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…This provides an evidence of the involvement of a single hydrogen atom into the defects, which give rise to the H 1 and H 2 traps. Finally, a good correlation has been found between the intensity of the LVM band with its maximum at 1104 cm −1 observed in the infrared absorption spectra of carbon and oxygen rich samples subjected to different heat‐treatments in the temperature range 550–700 °C and magnitudes of the MCTS signals due to the H 1 /H 2 traps in similarly heat‐treated neighboring samples, which were hydrogenated and prepared for MCTS measurements . The band at 1104 cm −1 is related to an LVM of the CO complex .…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…This provides an evidence of the involvement of a single hydrogen atom into the defects, which give rise to the H 1 and H 2 traps. Finally, a good correlation has been found between the intensity of the LVM band with its maximum at 1104 cm −1 observed in the infrared absorption spectra of carbon and oxygen rich samples subjected to different heat‐treatments in the temperature range 550–700 °C and magnitudes of the MCTS signals due to the H 1 /H 2 traps in similarly heat‐treated neighboring samples, which were hydrogenated and prepared for MCTS measurements . The band at 1104 cm −1 is related to an LVM of the CO complex .…”
Section: Resultsmentioning
confidence: 58%
“…Furthermore, it has been found that the H 1 /H 2 traps anneal out in the temperature range from 150 to 200 °C and their elimination resulted in significant improvement of lifetime in silicon wafers (see Refs. and ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…127,238 Recent publications have highlighted the role of hydrogen in performance limiting defects in n-type Cz silicon through the formation of a COH complex. 239,240 A thorough review of hydrogen-related defects is presented by A. Peaker et al in Chapter 2 of Fleetwood et al 241 Of particular importance for silicon solar cells, an increasing number of publications are highlighting the likely role of hydrogen in activating LeTID. [242][243][244][245][246][247] In particular, many of the behaviours of LeTID are consistent with the behaviour of hydrogen, such as the increased introduction of hydrogen with increasing firing temperature, 227 the ability to generate H 0 in the dark at low temperatures and induce the degradation without excess minority carriers, and the ability to cause the degradation in practically any commercially available silicon material for solar cells.…”
Section: Advanced Hydrogenation Of Silicon Solar Cellsmentioning
confidence: 99%
“…There are also uncertainties as to the impact carbon has in reducing the lifetime of silicon. For example, recent work has identified the formation of strong recombination active carbon-oxygen-hydrogen complexes in n-type silicon [68]. Therefore, the co-doping of boron-doped ingots with germanium or carbon does not appear to be a viable solution for completely avoiding B-O related degradation, without introducing other performance limiting defects.…”
Section: Additional Non-boron Related Doping During Crystal Growthmentioning
confidence: 99%